Long-term bond strength of adhesive systems applied to etched and deproteinized dentin - Ninoshka Uceda-Gómez; Alessandro Dourado Loguercio; Sandra Kiss Moura; Rosa Helena Miranda Grande; Margareth Oda; Alessandra Reis (University of São Paulo, 2007)
The aim of this study was to evaluate the early and 12-month bond strength of two adhesive systems (Single Bond-SB and One Step-OS) applied to demineralized dentin (WH) and demineralized/NaOCl-treated dentin (H). Twenty flat dentin surfaces were exposed, etched, rinsed and slightly dried. For the H groups, a solution of 10% NaOCl was applied for 60 s, rinsed (15 s) and slightly dried. The adhesives were applied according to the manufacturer's instructions and composite resin crowns were incrementally constructed. After 24 h (water-37ºC), the specimens was sectioned in order to obtain resin-dentin sticks (0.8 mm²). The specimens were tested in microtensile (0.5 mm/min) immediately (IM) or after 12 months of water storage (12M). The data (MPa) were subjected to ANOVA and Tukey's test (a=0.05). Only the main factors adhesive and time were significant (p=0.004 and p=0.003, respectively). SB (42.3±9.1) showed higher bond strengths than OS (33.6±11.6). The mean bond strength for IM-group (42.5±8.7) was statistically superior to 12M (33.3±11.8). The use of 10% NaOCl, after acid etching, did not improve the immediate and the long-term resin-dentin bond strength.